"Everything is now in order" – Groupthink, ideology and practical-critical activity in the European financial crisis and beyond. Issue 9 (1st September 2020) - Brunkhorst, Hauke
ABSTRACT: The present blockade of political action in the EU can be explained by a fatal combination of elite groupthink on the one hand and the constitutionalization of an ideology centred on the spontaneous evolution of market forces on the other. The different reactions on each side of the Atlantic to the crisis of 2008 revealed the truth that evolutionary theory cannot relieve us from 'living forward', taking political action that either emancipates us from socially-embodied ideology or fails to.